Evaluation of the geriatric co-management for patients with fragility fractures of the proximal femur (Geriatric Fracture Centre (GFC) concept): protocol for a prospective multicentre cohort study. Issue 7 (12th July 2017) - Joeris, Alexander; Hurtado-Chong, Anahí; Hess, Denise; Kalampoki, Vasiliki; Blauth, Michael
Abstract : Introduction: Treatment of fractures in the elderly population is a clinical challenge due partly to the presence of comorbidities. In a Geriatric Fracture Centre (GFC), patients are co-managed by a geriatrician in an attempt to improve clinical outcomes and reduce morbidity and mortality. Until now the beneficial effect of orthogeriatric co-management has not been definitively proven. The primary objective of this study is to determine the effect of GFC on predefined major adverse events related to a hip fracture compared to usual care centres (UCC). The secondary objectives include assessments in quality of life, patient-reported outcomes and cost-effectiveness. Methods and analysis: Two hundred and sixty-six elderly patients diagnosedwith hip fracture and planned to be treated with osteosynthesis or endoprosthesis in either a GFC or UCC study site will be recruited, 133 per type of centre. All procedures and management will be done according to the site's standard of care. Study-related visits will be performed at the following time points: preoperative, intraoperative, discharge from the orthopaedic/trauma department, discharge to definite residential status, 12 weeks and 12 months postsurgery. Data collected include demographics, residential status, adverse events, patient-reported outcomes, fall history, costs and resources related to treatment. The risk of major adverse events at 12 months will be calculated for each centre type; patient-reported outcomes will be analysed by mixed effects regression models to estimate differences in mean scores between baseline and follow-ups whereas cost-effectiveness will be assessed using the incremental cost-effectiveness ratio. Ethics and dissemination: Ethics approval for this study was granted from the local Ethics Committees or Institutional Review Board from each of the participating sites prior to patient enrolment. The results of this study will be published in peer-reviewed journals and presented at different conferences. Trial registration number: ClinicalTrials.gov: NCT02297581 ; pre-results.